CURRENT TRENDS IN TRANSFORMATION PRODUCTION AND CONSUMPTION WASTE MANAGEMENT SYSTEMS - E. Kalashnikova; I. Merkulova; O. Chuvilova (Вестник Северо-Кавказского федерального университета, 2022)
Based on the identification of problems of production and consumption waste management in Russia, an expert assessment of the regional program «Waste» was made. The ranking of economic mechanisms for managing production and consumption waste is presented, depending on the socio-legal and economic conditions. The scale of the solution of the tasks set is due to the fact that in the field of effective management of production and consumption waste, there are problems of both subjective and objective nature, and ways to overcome them in the possibility of a qualitative assessment. The results of a multi-criteria analysis of the effectiveness of applying a group of six main economic mechanisms in the field under study are presented.